Organ-specific phytohormone synthesis in two Geranium species with antithetical responses to far-red light enrichment - Gommers, Charlotte M M; Buti, Sara; Tarkowská, Danuše; Pěnčík, Aleš; Banda, Jason P; Arricastres, Vincent; Pierik, Ronald (Plant direct, 2018)
Plants growing in high densities experience a reduced red (R) to far-red (FR) light ratio and shade-intolerant species respond with accelerated elongation growth to reach the top of the canopy: the shade avoidance syndrome (SAS). FR-enriched light inactivates phytochrome photoreceptors, which results in subsequent action of several plant hormones regulating growth. SAS is adaptive for shade-intolerant plants, but is suppressed in shade-tolerant plant species. Inspired by a previously published transcriptome analysis, we use two species of the genus Geranium here to study the involvement of auxin, brassinosteroids (BRs), and gibberellins (GAs) in supplemental FR-induced elongation growth. G. pyrenaicum, a shade-avoiding species, strongly induces auxin and gibberellin levels, but not BR, in elongating petioles. We show that, in this species, FR light perception, hormone synthesis, and growth are local and restricted to the petiole, and not the leaf lamina. Using chemical hormone inhibitors, we confirm the essential role of auxin and GAs in supplemental FR-induced elongation growth. Shade-tolerant G. robertianum does not display the change in hormone levels upon FR light enrichment, resulting in the lack of a shade avoidance response.
Keywords: auxin; phytochrome signaling; brassinosteroids; Geranium; shade avoidance; gibberellins